160k views
0 votes
Ise the terms 4, 12a, 6, 2a, and 24 to make equivalent expressions

1 Answer

2 votes

Answer:

12a + 24 = 6(2a + 4) is the equivalent expressions

Explanation:

Given the terms ; 4, 12a, 6, 2a, and 24

There are two terms with unknown = 12a and 2a

but 12a = 2a x 6 .........(1)

from the last term = 24 = 6 x 4 ...........(2)

add both equation 1 and 2 = 12a + 24

12a + 24 = 6(2a + 4) is the equivalent expressions .

to VERIFY; Use a = 2

substitute into the expression ; LHS = RHS

= 12(2) + 24 = 24 + 24 = 48 (LHS)

FOR RHS = 6(2a+4) = 6(2x2 + 4)

= 6(4+4) = 48

Hence LHS = RHS

User Slanden
by
6.8k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.